(untitled) (Journal of Universal Science Research, 2024)
In the conducted field experiment, three different densities of cotton bushes (80, 100 and 120,000 per 1 ha, as well as 7.2, 9.0 and 10.8 plants per 1 running meter, respectively), two types of irrigation depending on the limited field moisture. the power of the soil (NPK) regime (70-70-60 and 75-75-60%, as well as the irrigation regime 2-3-0 and 2-4-0, respectively) and the mutual proportions of fertilizers (NPK) in two standards (1: 0.7:0.5 and 1:1:0.5). The annual fertilizer rates were: N200 P140 and K100 and N200 P200 and K100 kg/ha. It was taken into account that the yield of cotton grown under the conditions of 70-70-60% of the soil NVAC (limited field capacity) in the irrigation regime was higher than the yield of 75-75-60% of the irrigated options. during the years of experimentation. At 70-70-60% irrigation regime, depending on the density of the bush and the ratio of fertilizers, the average yield was 35.7-40.9 t/ha, and at 75-75-60% irrigation regime, the average yield by options was 33.2- 36.4 q/ha. It was found that the microneuron index of cotton fiber harvested from the experimental options was 4.3-4.5, and the microneuron index of cotton fiber harvested from the variants irrigated in the 70-70-60% mode was slightly higher than in the irrigation mode 75-75-60%.